2018
DOI: 10.1186/s40659-018-0160-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of downregulation of Stathmin gene on biological behaviors of U373 and U87-MG glioblastoma cells

Abstract: BackgroundStathmin as a critical protein involved in microtubule polymerization, is necessary for survival of cancer cells. However, extremely little is known about Stathmin in glioblastoma. So, this study was designed to elucidate the function of Stathmin gene in the tumorigenesis and progression of glioblastoma cells.MethodThe lentiviral interference vector pLV3-si-Stathmin targeting Stathmin gene and the control vector pLV3-NC were established for the co-transfection of 293T cells together with the helper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…37 Furthermore, some researchers demonstrated that the downregulation of STMN1 expression was capable of inhibiting the migration and invasion of cancer cells. 14,52,53,56 Overall, these previous studies support the notion that STMN1 may act as an oncogene and plays a pivotal role in promoting cancer progression, indicating that STMN1 may be a useful prognostic biomarker and therapeutic target. Consistently, accumulating evidence has suggested that elevated STMN1 expression is closely correlated not only with the development and progression of cancer, 10,11 but also with poor survival.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…37 Furthermore, some researchers demonstrated that the downregulation of STMN1 expression was capable of inhibiting the migration and invasion of cancer cells. 14,52,53,56 Overall, these previous studies support the notion that STMN1 may act as an oncogene and plays a pivotal role in promoting cancer progression, indicating that STMN1 may be a useful prognostic biomarker and therapeutic target. Consistently, accumulating evidence has suggested that elevated STMN1 expression is closely correlated not only with the development and progression of cancer, 10,11 but also with poor survival.…”
Section: Discussionsupporting
confidence: 69%
“…[49][50][51] Similarly, STMN1 downregulation could also inhibit the proliferation of glioblastoma cells and esophageal squamous cell carcinoma. 14,52 Additionally, several previous studies revealed that silencing the expression of STMN1 promoted cellular apoptosis of glioma, 50 oral cancer, 53 prostate cancer, 54 non-small cell lung cancer, 55 and esophageal squamous cell carcinoma. 37 Furthermore, some researchers demonstrated that the downregulation of STMN1 expression was capable of inhibiting the migration and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the poor therapeutic effect of chemotherapy, early radiotherapy, and late adjuvant therapy on malignant glioma, these treatments also have toxic side effects. Therefore, identifying new therapeutic agents to improve the prognosis of patients with malignant glioma is critical [10,11] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the poor therapeutic effect of chemotherapy, early radiotherapy, and late adjuvant therapy on malignant glioma, these treatments also have toxic side effects. Therefore, identifying new therapeutic agents to improve the prognosis of patients with malignant glioma is critical [12,13] . To overcome the limitations of the existing treatment methods for malignant glioma, many new treatment methods such as molecular targeted therapy, immunotherapy, gene therapy, stem cell therapy, and nanotechnology have begun to appear in preclinical and clinical research.…”
Section: Discussionmentioning
confidence: 99%